Estudo de líquidos iônicos próticos e surfactantes baseados em ácidos graxos para aplicação em remediação de derramamento de petróleo - Ribeiro, Sádwa Fernandes (2023)
Oil spills are increasingly frequent and responsible for damage to the environment. In this sense, the use of surfactants has emerged as an effective remediation method. However, conventionally applied dispersants present high toxicity, which may aggravate the environmental impact. In this context, the surfactant properties of protic ionic liquids and solutions based on fatty acids and monoethanolamine were studied in order to apply them in the remediation of oil spills. Thus, the ionic liquids (ILs) butyrolactam butyrate (BTB), 2- hydroxyethylammonium acetate (2-HEAA), 2-hydroxyethylammonium propanoate (2- HEAP) and choline laurate (LAU-CO) were synthesized using neutralization reaction. The synthesis was confirmed by Fourier Transform Infrared Spectroscopy (FTIR) and Nuclear Magnetic Resonance (NMR) and the ILs were characterized in terms of density and viscosity. Surfactant solutions based on monoethanolamine, lauric acid and oleic acid were prepared. Its surface-active properties were evaluated using surface tension and emulsification index. These analyzes indicated that the LIs BTB, 2-HEAA and 2-HEAP did not show good surfactant properties, thus being disregarded in the other experiments. LAU-CO and monoethanolamine and fatty acid solutions (MEA-AL and MEA-AO) reduced the tension of deionized water by more than 50% and showed critical micellar concentrations (CMC) of 29.9 mmol/L, 8.5 mmol/L and 1.2 mmol/L, respectively. Furthermore, they produced stable emulsions with motor oil and kerosene after 24 h. The surfactants that showed the best surfactant properties were evaluated for their ability to remove hydrocarbons from sand at ½ the CMC, at the CMC and 3 times the CMC. At this last concentration, removals of 67.44% ± 0.02, 57.03% ± 0.03 and 61.67% ± 0.05 were achieved for LAU-CO, MEA-AL and MEA-AO, respectively. The oil displacement area analysis indicated that the surfactants were able to disperse the oil, with LAU-CO standing out, dispersing 59.5 cm² in a total area of 63.6 cm². The LAU-CO, MEA-AL and MEA-AO surfactants were not toxic to the microcrustacean Artemia salina, with LC50 values of 763 µg/mL, 2057 µg/mL and 1956 µg/mL, respectively. In view of the above, the surfactants based on oleic and lauric acids in this study showed good surfactant properties and were promising for application in oil spill remediation.